2023
DOI: 10.3390/pharmaceutics15030761
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Action of SAAP-148 Antimicrobial Peptide as Studied with NMR and Molecular Dynamics Simulations

Abstract: Background: SAAP-148 is an antimicrobial peptide derived from LL-37. It exhibits excellent activity against drug-resistant bacteria and biofilms while resisting degradation in physiological conditions. Despite its optimal pharmacological properties, its mechanism of action at the molecular level has not been explored. Methods: The structural properties of SAAP-148 and its interaction with phospholipid membranes mimicking mammalian and bacterial cells were studied using liquid and solid-state NMR spectroscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 113 publications
0
0
0
Order By: Relevance
“…Side-chain RMSD is 3.65 Å and 3 Å in the DPC micelle and the POPC bilayer respectively. This result is in good correlation with published data: (i) other molecular dynamics studies revealed that the antimicrobial peptides SAAP-148 [10] and hylaseptin-4 [13] stabilize their helical conformations when interacting with DPC micelles; (ii) circular dichroism data revealed helical structure for the antimicrobial peptide anoplin when interacting with DPC micelle and POPC:POPG liposomes [40].…”
Section: Structural Analysis Of the Peptidesupporting
confidence: 90%
See 1 more Smart Citation
“…Side-chain RMSD is 3.65 Å and 3 Å in the DPC micelle and the POPC bilayer respectively. This result is in good correlation with published data: (i) other molecular dynamics studies revealed that the antimicrobial peptides SAAP-148 [10] and hylaseptin-4 [13] stabilize their helical conformations when interacting with DPC micelles; (ii) circular dichroism data revealed helical structure for the antimicrobial peptide anoplin when interacting with DPC micelle and POPC:POPG liposomes [40].…”
Section: Structural Analysis Of the Peptidesupporting
confidence: 90%
“…Concerning the interactions between interfacial anchored peptides and POPC bilayers or DPC micelles, most of the experimental studies give atomic description of the peptide structure. Only in few studies, the specific interactions between the peptide and the DPC or POPC molecules are described [9,10]. Indeed, such experimental information is scarce due essentially to the unfavourable dynamics of the systems, especially at the membrane interface where the dynamics of the lipid head groups is important.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are necessary to elucidate the specific mechanisms and contributions of these interactions in the antimicrobial and immunomodulatory activities of these peptides. Although both peptides are alpha helical [32,53], further studies are needed to elucidate differences in amphipathicity and stability of alpha helices with respect to membrane-peptide interactions.…”
Section: Discussionmentioning
confidence: 99%